CRITICAL REVIEW OF MEDA DHATU AND OBESITY IN REFERENCE TO AYURVEDIC LITERATURE - Anand, Rahul; Asthana, Alok; Asthana, Monika; Sabharwal, Pooja (Asian Journal of Pharmaceutical Research and Development, 2018)
Obesity is one of the santarapanajanya vyadhi, originated as a result of deteriorated life style which includes sedentary daily routine and junk food habits. It occurs when the consumption of calories becomes more than its expenditure. It serves as an etiological factor for many diseases. It has reached to the epidemic proportion, affecting majority of the urban population. Obesity can be estimated by various scales among which Body Mass Index (BMI) and skin fold measurements are most common. Obesity is indirectly proportional to Basal Metabolic Rate (BMR). BMR is the amount of energy required to do the involuntary work of the body which is around 47 calories per hour per square meter of body surface in males and 37 in females, but may vary with temperature as a rise in 1o F of body temperature may lead to an average increase of 7% of BMR1. Prior to the management of this disorder, it is obligatory to reach to its roots. Ancient scholars tried to elaborate the causes, pathology, types, complications and management of obesity in their own way, and this description is scattered here and there. The present article will try to assemble these references, and find out a common conclusion.